2016
DOI: 10.1007/s00417-016-3489-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fixed-dosing aflibercept for treating polypoidal choroidal vasculopathy: 1-year results of the VAULT study

Abstract: PurposeTo investigate fixed-dosing aflibercept for treating polypoidal choroidal vasculopathy (PCV).MethodsThis phase IV, prospective, single-arm, interventional case series was conducted in eight centers. Forty treatment-naïve PCV patients were administered three monthly doses of intravitreal aflibercept (2.0 mg) and an injection every 2 months thereafter. Best-corrected visual acuity (BCVA) and central subfield macular thickness (CSMT) were measured at each visit. Fluorescein and indocyanine green angiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
36
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 21 publications
4
36
2
Order By: Relevance
“…On the other hand, ranibizumab monotherapy only demonstrated a 5-letter improvement in the LAPTOP study [10]. Our results are consistent with those of the Vault study, which showed an improvement of 9 letters after 1 year of follow-up in PCV patients treated with bimonthly aflibercept [17]. Our study also showed that VA improvement could be rapidly achieved with a gain of 8.6 letters at 2 months after treatment beginning.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…On the other hand, ranibizumab monotherapy only demonstrated a 5-letter improvement in the LAPTOP study [10]. Our results are consistent with those of the Vault study, which showed an improvement of 9 letters after 1 year of follow-up in PCV patients treated with bimonthly aflibercept [17]. Our study also showed that VA improvement could be rapidly achieved with a gain of 8.6 letters at 2 months after treatment beginning.…”
Section: Discussionsupporting
confidence: 89%
“…However, most of the previous studies had been performed in Asian populations since the prevalence of PCV is significantly higher than in the Caucasian population [2, 17, 18]. This study demonstrates clinical and functional outcomes in a Caucasian population comparable to those of Asian populations [17].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Our BCVA improvement results were very similar to the results of IVA in Japanese PCV patients using a proactive fixed dosing regimen reported by Yamamoto et al [17] . The results of the current study pertaining to the proportion of patients in which BCVA either remained stable or improved (97.6%) were also similar to results reported in the VAULT study in Korea (87.5%) [20] . Our results were also similar to those of the 2q8 regimen group of the VIEW study [15,16] , which included both PCV and typical AMD (95.6%).…”
Section: Discussionsupporting
confidence: 87%
“…In the VAULT study, Lee et al [20] reported 1-year results of IVA in 40 treatment-naïve PCV patients receiving bimonthly injections after 3 initial monthly injections, and mean BCVA improved from 55.1 to 64.2 letters (ET-DRS chart). They also reported that 87.5% of the patients exhibited maintained or enhanced BCVA at 12 months.…”
Section: Discussionmentioning
confidence: 99%